Evaluasi Pengalaman Pengguna Aplikasi E-Peken Surabaya Menggunakan Metode User Experience Questionnaire (UEQ) - Diva Dafina Amajida; Pratama, Arista; Suryanto, Tri Lathif Mardi (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
Current technological developments make it easier for people to fulfill various needs more easily, efficiently, and quickly. One example is e-commerce. The Surabaya City Government launched the E-Peken Surabaya application in 2021 to support MSMEs, grocery stores, and Culinary Tourism Centers (SWK) in Surabaya. The main goal of E-Peken Surabaya is to boost the local economy affected by the COVID-19 pandemic. Despite its conveniences, this application faces user experience issues, such as malfunctioning features, inefficient systems, limited payment methods, and a monotonous impression. This study evaluates the user experience of E-Peken Surabaya using the User Experience Questionnaire (UEQ) method. Sampling involved 375 City Government ASNs who use E-Peken. Data was analyzed using the UEQ Data Analysis Tool. The results show an average value on the Attractiveness scale of 1.87, Clarity 1.86, Efficiency 1.80, Accuracy 1.70, Stimulation 1.76, and Novelty 1.52. The correlation test showed all scales were >0.70, indicating high reliability. The Attractiveness scale scored the highest, showing users liked the overall app impression. In contrast, the Novelty scale scored the lowest, indicating users did not perceive the app's uniqueness compared to other e-commerce. These findings highlight areas for improvement to enhance the user experience of E-Peken Surabaya.